Acumulación de ácido araquidónico en fosfolípidos y triglicéridos y producción de prostaglandinas con relación a estrés térmico en semilla de ostión Crassostrea gigas - Duran Encinas, Yazmin (Centro de Investigaciones Biológicas del Noroeste, 2020)
Crassostrea gigas is a marine invertebrate that inhabits the intertidal zone and therefore, is commonly exposed to multiple environmental stressors, including temperature. In recent years mass mortality events have been reported in Mexico in C. gigas associated with the increase in temperature during the summer. Organisms under thermal stress present an increase in prostaglandins (PG) production by cyclooxygenases (COX), an enzymatic route using arachidonic acid (ARA) present in the phospholipids (FL) of the cell membrane as substrate, but PG can also increase non-enzymatically by reactive oxygen species (ROS) that are produced during increased metabolism. It has been reported that some organisms exposed to stress accumulate a higher concentration of ARA in triglycerides (TG) and concluded that this could be a mechanism to avoid the unregulated production of PG. The aim of the present study is to evaluate if ARA from diet accumulates in TG or FL and if a thermal stress promotes the transfer of ARA from TG to FL to increase PG production in oyster C. gigas. To demonstrate our hypothesis, oyster seeds C. gigas were acclimated at 20°C and fed with Chaetoceros calcitrans microalgae labeled with 13C. Oyster seeds were subjected to cyclic thermal stress with a temperature increase of 15ºC daily (from 20 to 35ºC) and subsequently a gradual decrease to 20°C, for 4 days. Oyster seed kept at 20°C was used as control. At the end of the experiment, samples were taken for analysis of fatty acids, stable isotopes, PG, gene expression (heat shock proteins (HSP70), antioxidant enzymes (SOD and GST) and stress proteins (IOC and GS), and histology. The oyster seeds exposed to thermal stress showed a decrease in the height of the epithelium of the digestive tubules, as well as a greater hemocyte count in the connective tissue using histology, higher levels of PGEM and an increase in expression levels in all the different genes evaluated in this work. ARA concentration in TG decreased compared to the control group, while in FL ...